The status of prisoners-of-war under international law: an analysis of the Afghan scenario - Eishan Jan, Mohammad Naqib (International Islamic University Malaysia, 2002)
In the course of military operation against the Taliban regime and its foreign allies, including al-Qaeda, thousands of combatants were captured and detained bu anti-Taliban Afghan forces and by the United States. The United States brands the prisoners as "unlawful combants", refuses to give them prisoners-of-war status, to grant them access to a lawyer or to bring them before a 'competent tribunal' and consequently denies them all the rights and privileges that are provided under the international humanitarian laws, and the most relevant of these laws are the four Geneva Conventions of 1949, to which almost all states, including the United States and Afghanistan are parties, and the two 1967 Protocols Additional to the Geneva Conventions. A study of the relevant provisions of these laws reveal that the detainees in the custody of the United States in Afghanistan and Guantanamo Bay do qualify for prisoners-of-war status and as such they are entitled to all the rights and privileges that are provided under the Third Geneva Conventions Relative to the Treatment of Prisoners-of-war. If the United States has, however, doubts as to whether the captives deserve prisobers-of-war status, it should not act arbitrarily but let the issue to be decided by a competent tribunal and should allow the prisoners to enjoy the protection of the Third Geneve Convention until their status is determined by the said tribunal. This is the requirement of the said Convention and the detaining powers must ensure that all their actions in relation to the detainees comply with the intetnational law standards for it is crucial is justice is to be done and seen to be done, and if respect for the rule of law and human rights is not to be undermined.